Anthropodermic Bibliopegy, or, Using Human Skins in Books Binding: A historical study - د. حامد معروف الزیات (المجلة الدولية لعلوم المكتبات والمعلومات)
This study discuss the history of ‘Book Binding Phenomenon’ which meanthat using human skin in binding books. This Phenomenon has been appeared,virtually, during the 16th century, began in the 19th century and had disappearedat the beginning of the 20th century. The motivations of this phenomenon havebeen varied between a punishment of the guilty criminals and a desire of somepeople to prevent their skin from decomposition after death, also the marginalizedand the poor, in addition to the judicial decisions as a source of access to humanskin. That skin was drowned in known places such as the French city, "Midon",and by famous binders such as John Stockton Hog and Rapparlier who was thebinder of the book entitled "Dance of death". Doctors also took part in thispractice by their hands, but the collectors of the books kept it from extinction toappear in the modern era and cause a noise in the antique libraries which rose tosearch for these human covers by using advanced techniques as "massspectrometry analysis" in collaboration with prominent scientists as "Daniel P.Kirby."The study pointed to some people who used their skins in Binding ofbooks such as John Horwood, William Burke, etc., in completely absence of allreligious, morals and legal matters, whether by the courts or doctors. Despite theallegations surrounding binding of books with human skins generally, and someof them correctly proved, but others have not yet proved, just like a copy of the“Holy Quran” with the skin of an Arab sheikh named Bashir bin Salem al-Harthythat had been found in the Cleveland Public Library, U.S.A. However, there are alot of books all over the world that had been covered with human skin in differentsubjects and languages directions. According to language direction English camein first rank with 41%. In subject direction Medicine came first with 45.5%. Finally,by time line the 19th century came first with 59.1% from total number of bookswhich covered with human skin that included in the bibliography of the study, andcontained just twenty-